2010
DOI: 10.1007/s00134-010-2065-4
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous sildenafil for postoperative pulmonary hypertension in children with congenital heart disease

Abstract: PurposeTo evaluate the efficacy and safety of intravenous sildenafil for immediate postoperative pulmonary hypertension (PH) in pediatric patients undergoing congenital heart surgery.MethodsA double-blind, multicenter, placebo-controlled, dose-ranging, parallel-group trial was conducted. Patients were randomized to one of three doses of intravenous sildenafil, or placebo, for a minimum of 24 h.ResultsThe study was heavily underpowered. Whereas enrollment of 228 patients (57 per treatment arm) was required to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 21 publications
0
64
0
1
Order By: Relevance
“…Documented neuro-hormonal effects have been reported by Hulsmann, through a reduction of atrial natriuretic factor and norepinephrine on the one hand and increased renal blood flow, with increased diuresis [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Documented neuro-hormonal effects have been reported by Hulsmann, through a reduction of atrial natriuretic factor and norepinephrine on the one hand and increased renal blood flow, with increased diuresis [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…In 36 neonates with a mean age of 34 h and persistent PH (29 receiving concomitant inhaled NO), intravenous sildenafil by continuous infusion for at least 48 h and up to 7 days resulted in acute and sustained improvement in oxygenation (Steinhorn et al, 2009), with survival of 35 neonates at day 28. Intravenous sildenafil given for a minimum of 24 h, compared with placebo, also reduced mPAP and shortened time to extubation for immediate postoperative PH in a study of 17 children (median age, 5 months) with congenital heart disease (Fraisse et al, 2011). Another study showed that intravenous sildenafil augmented the pulmonary vasodilator effect of inhaled NO in 15 infants after cardiac surgery, but produced systemic hypotension and impaired oxygenation (Stocker et al, 2003).…”
Section: Label Expansion I Delay In Clinical Worseningmentioning
confidence: 98%
“…As described by Fraisse et al [1], maintenance infusions of sildenafil may have clear advantages. However, in order to correctly administer continuous i.v.…”
mentioning
confidence: 96%
“…Dear Editor, With great interest we read the paper of Fraisse et al [1] in which the authors document the intravenous (i.v.) use of sildenafil in paediatric patients with congenital heart disease and pulmonary hypertension.…”
mentioning
confidence: 99%
See 1 more Smart Citation